Isolating the malady, liberating the host - Tweedy, Lenska Simon (My University, 2017)
The aim of the facility being designed is to focus on the resident by utilizing healing architecture, the notion that architectural elements and design effect ones well being. The disease Tuberculosis will be used as a platform for this exploration. After much research, it is evident that the Tuberculosis (TB) problem is worse today due to inadequate health care facilities and ineffective treatment methods, which do not handle the issue with the urgency it deserves. Currently, TB is treated for a very limited period of time in hospitals. Once this time is up, most patients are able to return home where they have to be self medicated. This is a dangerous, expensive and unreliable practice, as neglecting to take ones medication regularly can result in other strains of TB being developed. This is clearly a weak and irresponsible method of treatment, and therefore this report proposes that the health sector returns to the traditional methods of treating the disease, which is through isolation and a long period of confinement in a recovery setting. This investigation will be performed through analysing forms of health architecture and how to achieve a humane space for long term patients. Plants featured strongly in this investigation, and therefore research into the role planting has in healing architecture has been emphasised.
Thesis is submitted in partial fulfilment for the degree of Master of Architecture (Professional) to the Faculty of Engineering and the Built Environment, School of Architecture and Planning at the University of the Witwatersrand, Johannesburg, 2017
Keywords: City planning--South Africa--Johannesburg; Hospital buildings--Design and construction; Hospital architecture--Designs and plans; Architectural design--Health aspects